2010
DOI: 10.1371/journal.pone.0010930
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Serious Illnesses in Rural Cambodia: A Cross-Sectional Survey

Abstract: BackgroundThere is substantial evidence that ill-health is a major cause of impoverishment in developing countries. Major illnesses can have a serious economic impact on poor households through treatment costs and income loss. However, available methods for measuring the impact of ill-health on household welfare display several shortcomings and new methods are thus needed. To understand the potential complex impact of major illnesses on household livelihoods, a study on poverty and illness was conducted in rur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 25 publications
3
27
0
Order By: Relevance
“…The similarity in the conditions recorded in the present study across the five quintiles of household wealth was less expected, since poverty often appears to help to perpetuate illness. 1,2,5 Although the members of the households that we surveyed were able to obtain care for most of their episodes of illness, 13% of them were forced to adopt "distress" financing to cope with the costs of the care. In Bangladesh, where an estimated 65% of health-care expenditure is financed from out-of-pocket payments, illness is a major cause of economic hardship and poverty.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The similarity in the conditions recorded in the present study across the five quintiles of household wealth was less expected, since poverty often appears to help to perpetuate illness. 1,2,5 Although the members of the households that we surveyed were able to obtain care for most of their episodes of illness, 13% of them were forced to adopt "distress" financing to cope with the costs of the care. In Bangladesh, where an estimated 65% of health-care expenditure is financed from out-of-pocket payments, illness is a major cause of economic hardship and poverty.…”
Section: Discussionmentioning
confidence: 99%
“…Data on sociodemographic status, household expenditure and illness experienced in the previous 30 days were collected. All illnesses were coded according to a disease list that had been developed in previous studies 2,7,10,22,23 and finalized after pilot testing in 100 households (Appendix A). Data were collected on the time of onset and, if possible, duration of illness, diagnosis, treatment response, treatment cost and coping strategies.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…With recent evidence highlighting the prevalence of hypertension and related metabolic disorders in Cambodia,1 2 attention is now being given to initiating evidence-based prevention and control strategies. A national survey in 2010 revealed that hypertension had an urban prevalence of approximately 16.90%, a rural prevalence of 10.00%, and overall country prevalence of 11.20% among persons aged 25–64 years 3…”
Section: Introductionmentioning
confidence: 99%